Clinical features of people with hip-related pain, but no clinical signs of femoroacetabular impingement syndrome. (November 2018) - Retchford, Timothy H.; Tucker, Kylie J.; Weinrauch, Patrick; Cowan, Sallie M.; Grimaldi, Alison; Kemp, Joanne L.; Crossley, Kay M.
Abstract: Objectives: Identifying impairments in hip range of motion (ROM) and muscle strength in people with hip-related pain, without signs of femoro-acetabular impingement syndrome (FAIS). Study aims: to determine if hip strength and ROM i) differs between the symptomatic and less-symptomatic hip of people with hip-related pain; and between people with hip-related pain and healthy controls; and ii) are associated with hip-related Quality of Life and pain. Design: Cross-sectional study. Setting: University laboratory. Participants: Thirty participants with hip-related pain who were awaiting hip arthroscopy (22 women; age = 37 ± 10yrs), 32 healthy controls (19 women; age = 30 ± 10yrs). Main outcome measures: Hip ROM, muscle strength, pain intensity and the Hip disability and Osteoarthritis Outcome Score (HOOS) were assessed. Results: Less hip flexion ROM (p = 0.004), and extension (p = 0.004), abduction (p = 0.001) and internal rotation (IR) (p = 0.048) strength were measured on the symptomatic compared to non-symptomatic side. Hip-related pain participants had lower hip abduction strength (p = 0.045), and less flexion (p < 0.001), IR (p = 0.027) and external rotation (ER) (p = 0.019) ROM compared to controls. Less ER ROM (p = 0.03–0.04), and greater abduction (p = 0.03–0.04) and adduction strength (p = 0.02) were associated with better patient reported outcome measures. Conclusions: Specific impairments in hip ROM and strength were identified in people with hip-related pain but no FAIS. Highlights: People with hip-related pain, but not FAIS, have impairments in ROM and strength, when compared to the other hip, and to pain-free participants. This is despite no signs of FAIS. People with hip-related pain who had less ER ROM, and greater hip abduction and adduction strength had better PROMs.